Rivisit grid computing security - Ismail, Saiful Adli (Penerbit UTM Press, 2008)

(untitled)
Recent studies have shown that Grid Computing provide computational power, data storage and network bandwidth of under utilized resources at a minimal cost to the end user. It integrates geographically distributed resources and perform collaborative task. Since the goal of grid is resource sharing, computer resource will be accessed by a lot of users from different virtual organizations (YO). The security requirement becomes more vital to the Grids. Securities playa major role in providing the confidentiality of the communication, the integrity of data and the privacy of the user information. This paper focuses on to define current grid security issues and address grid security problem and challenges.